Ball workers or system hostages? The trajectory of the football athlete in the field demarced by the interests of capital - Kupper, Agnaldo [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2024)
To understand football, it is necessary to know and recognize the position that the activity occupies through the distribution of practitioners according to their placement in the social space, pointing to the need to perceive the treatment of the sport as a phenomenon inscribed in a market system. capitalist relations, adapting to modern life and establishing itself as a disguised form of work, following the determinations dictated by production. In the process of transforming football into a globalized sporting spectacle, athletes are seen as merchandise, fans as consumers and the game as a financial asset.
Keywords: Football; Industrialism; Key words; Work relationships